The use of Facebook in a community pharmacist-led weight management programme – a London-based proof of concept study. (26th March 2021) - Crilly, P; Chibueze, E; Khan, M; Modha, J; Satwaha, S; Sherpa, N; Kayyali, R
Abstract: Introduction: In the United Kingdom (UK), 63% of adults are overweight, (1) costing the NHS £6.1 billion/year. With the public using digital technology over healthcare professionals (HCPs) for health advice, this warrants an investigation of technology use in community pharmacy, given its previous successful use.(2) Aim: To determine the feasibility and perceptions of a community pharmacist (CP)-led weight management programme (WMP), enhanced by a Facebook support group (FSG). Methods: A proof of concept study was conducted between January-March 2020. Recruitment was via a pharmacy, the university and a community Facebook group. Inclusion criteria: over 18 years; overweight; no medical conditions. Participants attended face-to-face meetings (ftf) with a CP and final year pharmacy student (PS) on two occasions (0 (baseline) and 4 weeks). At baseline, participants were given the NHS weight loss programme and set weight loss goals. During ftf, participants had height, weight, and waist circumference (WC) measurements by a CP/PS and discussed eating habits, exercise and alcohol. In between ftf, participants accessed the FSG (created (December 2019) and moderated by a CP). Here, they received posts about diet, exercise and motivation. Participants were to have their measurements taken ftf at 8-weeks, however, COVID-19 meant participants had to self-declare these via video call. Following the 8-week programme, participants completed a 4-section survey about their experience (signing up to the service; comparison to previous weight loss attempts; the FSG and overall perceptions). Question types included multiple choice, Likert scale and free text comments. Data were analysed in Excel (Microsoft Corporation 2016) with changes in height, weight, waist circumference, alcohol and exercise being calculated. Results: Fifty-five participants were recruited. 18 were lost to follow-up, most (n=12/18) citing COVID-19. Of the 37 participants remaining (70.3% female, mean age=37 years), 22 were obese, the rest overweight. Mean weight loss, mean percentage weight loss and mean WC reduction at 4-weeks was 1.6 kg (SD+/- 1.7 kg), 1.8% (SD+/- 1.9%) and 2 cm (SD+/- 1.96 cm) respectively. At week 8 measurements were self-declared. Mean weight loss at 8-weeks from baseline was 2.7 kg (SD +/- 2.6 kg) and mean percentage weight loss was 3% (SD+/- 3%). Only five participants' self-declared WC measurements at 8-weeks with mean reduction being 3.6 cm. Five participants moved to healthier BMI classifications by week 8. All participants accessed the FSG at least weekly with 13 accessing it daily. Diet posts were the most popular (n=20/37). Participants learned about portion control and increasing fruits/vegetables intake. All participants would recommend the programme to their friends/family. Conclusion: An 8-week CPWMP, enhanced with FSG, supported participants to lose a mean of 3% body weight. Participants accessed the page regularly and were positive about its usefulness. One limitation was that the COVID-19 lockdown prevented the 8-week ftf, therefore, self-declared measurements were used. The pandemic has highlighted the importance of pharmacy embracing technology for service delivery, particularly when in-person contact is limited. The implication of this study is that it provides proof that the concept of digital service delivery could work in practice. References: 1. GOV.UK. Tackling obesity: empowering adults and children to live healthier lives [Internet]. Department of Health and Social Care. 2020 [cited 2020 Aug 18]. Available from: https://www.gov.uk/government/publications/tackling-obesity-government-strategy/tackling-obesity-empowering-adults-and-children-to-live-healthier-lives 2. Crilly P, Kayyali R. A Systematic Review of Randomized Controlled Trials of Telehealth and Digital Technology Use by Community Pharmacists to Improve Public Health. Pharmacy 2020;8(3):137. Available from: https://www.mdpi.com/2226–4787/8/3/137